Analisis Efisiensi serta Efektivitas Zakat Aparatur Sipil Negara dan Zakat Digital terhadap Penerimaan Zakat di Baznas Provinsi Jawa Barat - Sa’atul Kamilah; Jalaluddin Jalaluddin (Ma'soem University, 2023)
This background reviews how to optimize the efficiency, effectiveness of ASN zakat and digital zakat on receiving zakat using information technology in processing data by the amil if it is wrong, errors can occur. This study aims to find out how the analysis of the efficiency and effectiveness of ASN zakat, and digital zakat, on zakat receipts at the Baznas of West Java Province for the 2018-2023 period. This research is a qualitative research with a descriptive approach. The data used is primary data, by taking information on the BAZNAS Amil of West Java Province. Data collection techniques used are observation, interviews, literature study, and documentation. The results of the study show that the Efficiency Effectiveness of ASN zakat based on interviews with the head of the Department of Collection of ASNs can directly pay zakat through the official Baznas website, namely baznasjabar.org/zakat. And the assessment of the ASN zakat source aspect has four points. Results for Digital Zakat based on interviews with Digital Staff can be channeled through the official website, namely baznasjabar.org/zakat. And using the Simba Zakat application, you can also go through Mobile Banking, pay with QRIS such as Gopay, Ovo, Link Aja, Funds, and can pay with one of the Shopee E-Commers. And the assessment of aspects of digital zakat has four points. The results of receiving zakat funds based on interviews with the Head of the Distribution Division were given to the eight asnaf by selecting those who were entitled to receive them, which was carried out by a competent amil. distribution of zakat funds refers to PSAK No.109 and Zakat Law Number 23 of 2011 concerning Zakat. And the assessment of the aspect of receiving zakat funds has six points.